Competencies of Healthcare Workers in Diabetic Ketoacidosis in Children - Muhiasen, Salam; Musihb, Zeki (Journal of Biomedicine and Biochemistry, 2024)
Background Diabetic ketoacidosis (DKA) is a severe, acute compli- cation of diabetes characterized by hyperglycemia, ketoacidosis, and ke- tonuria, posing a potentially fatal risk, especially in individuals with type 1 diabetes.Objective of the study The study aims to evaluate the knowledge of healthcare providers regarding pediatric DKA at Babylon Hospital for Maternal and Child.Methods A cross-sectional descriptive study design was employed from August 1, 2023, to March 1, 2024, involving the assessment of healthcare providers’ knowledge about DKA using a two-section questionnaire. Sec- tion one gathered sociodemographic data, while section two assessed knowl- edge about pediatric DKA. Convenience sampling included 100 healthcare providers. Both inferential and descriptive statistical analyses were applied to the data.Results The study revealed a significant relationship between health- care providers’ knowledge of DKA and their sociodemographic character- istics, including age, residency, marital status, educational level, work site, years of experience, and years of experience in the unit.Conclusion The findings suggest that the majority of healthcare providers exhibited moderate to poor levels of knowledge regarding the management of pediatric DKA.Recommendations It is imperative to implement targeted educa- tional programs and training sessions to enhance healthcare providers’ un- derstanding and management skills related to pediatric DKA. Additionally, continuous monitoring and evaluation of healthcare providers’ knowledge levels are essential to ensure optimal patient care outcomes.